Problematika Kewenangan Pemerintah Daerah di bidang Pertanahan - Farda, Nessa Fajriyana; Putra, Yosep Hadi (Pagaruyuang Law Journal, 2019)
Land is one important element for humans. That is how importance of land, the government needs to make special arrangements regarding use of the land. In general, land arrangements are regulated in Law Number 5 of 1960 concerning Basic Rules on Agrarian Matters, which stipulates that the authority in the field of land is the authority of the central government. In addition, Indonesia as a unitary state also adheres to the principle of decentralization, it means that the central government gives authority to the regions to regulate their own regional affairs, including of land matters. The regulation regarding of land authority for regional governments is described in Act Number 23 of 2014 concerning Regional Government. However, the application of its authority is not yet optimal, because there is no balance of relations between the central government and regional governments in regulating land. The problem discussed in this study is how the division of authority between the central government and regional government of land matters. The approach used in this research is normative juridical. In the other word, this study examines the problem based on applicable laws and regulations, especially regulations regarding land. The data is collected by using literature study, then analyzed and described systematically. The result showed a norm conflict in the division of land authority in the UUPA and the Regional Government Law. Therefore, it is hoped that there is a clear division of authority between the central and regional governments which is not only contained in the Regional Government Law.